Ag/VO2/Ag sandwich nylon film for smart thermal management and thermo-responsive electrical conductivity. Issue 1 (June 2022) - Peng, Linghui; Shen, Lingling; Fan, Weiren; Liu, Zichuan; Qiu, Hongbo; Yu, Aibing; Jiang, Xuchuan
Due to the effects of climate changing, the importance of outdoor thermal comfort has been recognized, and has gained more and more research attentions. Unlike indoor space where air conditioning can be easily implemented, outdoor thermal comfort can only be achieved by localized thermal management. Using textile is a simple but energy-saving way to realize outdoor thermal comfort. Herein, we report the design of a smart thermal management film with the silver/vanadium dioxide/silver (Ag/VO2 /Ag) sandwich structure prepared by one-dimensional (1 D) nanowires. It was found that the Ag/VO2 /Ag sandwich film was able to lower the temperature by around 10 °C under intense infrared (IR) radiation. In addition, the Ag/VO2 /Ag sandwich structure film showed a thermo-responsive electrical conductivity and an outstanding bending stability, due to network structure formed by nanowires. It was experimentally proved that this sandwich structure was superior to other layer structures in IR shielding performance and thermo-responsive electrical conductivity. The as-prepared Ag/VO2 /Ag sandwich structure film has great potential for various applications such as wearable devices, flexible electronics, medical monitors and smart IR radiation management.